The Digital Revolution in Higher Education: Transforming Teaching and Learning - Qolamani, Khalid Ilias Basheer; Mohammed, Mohammad Mahdi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Digital transformation in higher education has dramatically disrupted conventional teaching and learning models. This review traces the evolution of educational technology over the past few decades. It analyzes how tools such as learning management systems, data analytics, online learning, and artificial intelligence impact pedagogy, student experience, educator roles, and institutional learning. The great potential of technology to enhance learning is also discussed, along with the ongoing challenges of justice, ethics, and human relations in its application. Current and emerging technologies and their implications for key stakeholders are examined. This study uses a multi-faceted methodology to investigate digital transformation in higher education: Historical Analysis, Technology Review Case Studies, Stakeholder Surveys, and Ethical and Social Implications. Predictive modelling and trend analysis are performed to project higher education's future digital transformation trajectory, which includes analysis of new technologies, potential disruptions, and the evolving needs of the education sector. The review brings together insights from academic literature, industry publications, and the digital transformation of higher education over the past few decades, which has been widespread and measurable. Early adopters of technologies such as analytics, AI, and immersive media will be best positioned to improve the student experience in the future. However, carefully applying and considering students' needs and equality is essential to avoid marginalized groups.